BAKUNANAYS guidelines for communicating COVID-19 vaccination information to pregnant women in the Philippines and other developing countries - Cagayan, Maria Stephanie Fay Samadan; Mendoza, Lumberto G.; Viana, John Noel M. (Frontiers in Communication, 2022)
COVID-19 remains a pressing global health disaster, and pregnant women and their unborn child/ren continue to be extremely at risk. In the Philippines, a developing country in Southeast Asia, pregnant women were generally excluded from initial vaccination drives to avoid adverse effects in their offspring, amidst findings from animal studies and post-trial monitoring on the vaccines’ safety. In August 2021, the Philippine Obstetrical and Gynecological Society (POGS) and the Department of Health (DOH) released guidelines for the vaccination of pregnant women due to the eventual increase in their mortality during outbreaks of the Delta variant. This perspective presents various forms of scientific communication on COVID-19 vaccination to Filipino pregnant women and forwards recommendations to improve communication in various settings. First, we present three modalities on how information on COVID-19 vaccination is disseminated to pregnant women in the Philippines and discuss their potential impacts on knowledge promotion and actual vaccination uptake, taking into account the Filipino cultural value of “pakikipagkapwa”. These include government and doctor-led initiatives, social media posts and comments, and experiences of one of the authors in vaccination drives in rural and remote communities. Findings are used to develop the BAKUNANAYS framework, comprised of ten recommendations for healthcare workers, health agencies, and doctors vaccinating pregnant women in the Philippines and other developing countries, especially those with a similar socio-economic profile and cultural values.